2020
DOI: 10.1111/avsc.12490
|View full text |Cite
|
Sign up to set email alerts
|

Alien flora across European coastal dunes

Abstract: QuestionsThe spread of alien plant species is one of the main threats to the biodiversity of different natural habitats, and coastal dune habitats are among the most affected. There is a considerable local and regional variation in the level of alien plant invasion on coastal dunes. We asked what are the patterns of invasion across European coastal dunes and how they depend on habitat types and coastal regions.LocationAtlantic, Baltic, Black Sea and Mediterranean coasts of Europe.MethodsWe used vegetation‐plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 57 publications
10
49
0
1
Order By: Relevance
“…Among these, biodiversity in the Mediterranean Basin is particularly vulnerable because of intense human exploitation, land degradation (Hill et al, 2008;Underwood et al, 2009), and increasingly arid climatic conditions (Roy et al, 2019). The Mediterranean Basin is also threatened by alien plants moved around by long-distance trade exchanges (Seebens et al, 2018), as shown by global (Sala, 2000;Arianoutsou et al, 2013;Pyšek et al, 2017;Casado et al, 2018) and several regional studies (Chytrý et al, 2008;Carboni et al, 2010Vilà et al, 2011Ronk et al, 2017;Giulio et al, 2020). In particular, the European and Anatolian part of the Mediterranean Basin (further on "Mediterranean Europe") is considered at high risk of new invasions both under current (Brunel et al, 2010;Roy et al, 2019) and future (Gritti et al, 2006) climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, biodiversity in the Mediterranean Basin is particularly vulnerable because of intense human exploitation, land degradation (Hill et al, 2008;Underwood et al, 2009), and increasingly arid climatic conditions (Roy et al, 2019). The Mediterranean Basin is also threatened by alien plants moved around by long-distance trade exchanges (Seebens et al, 2018), as shown by global (Sala, 2000;Arianoutsou et al, 2013;Pyšek et al, 2017;Casado et al, 2018) and several regional studies (Chytrý et al, 2008;Carboni et al, 2010Vilà et al, 2011Ronk et al, 2017;Giulio et al, 2020). In particular, the European and Anatolian part of the Mediterranean Basin (further on "Mediterranean Europe") is considered at high risk of new invasions both under current (Brunel et al, 2010;Roy et al, 2019) and future (Gritti et al, 2006) climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the particularly noxious invasive plant species are species of the genus Carpobrotus (Aizoaceae), or ice plant (Giulio et al, 2020). Carpobrotus species are succulent perennial herbs native to South Africa, Australia or Chile, introduced outside of their native range for ornamental or soil stabilization purposes (Campoy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Another source of concern stems from biological invasions, which are deemed a severe threat to biodiversity (second only to habitat loss and fragmentation; DAISIE, 2009;Vilà et al, 2011;EEA, 2012). Coastal areas are often reported to host many alien species (Von Holle and Motzkin, 2007;Chytrý et al, 2008;Giulio et al, 2020) and are considered as one of the most invaded ecosystems worldwide (Dawson et al, 2017). Especially in sand dune habitats, alien species can exert strong ecological impacts (e.g.…”
Section: Introductionmentioning
confidence: 99%